The Correlation Between Students’ Attitudes Toward Technology-Mediated English Learning And Their English Achievement At Vocational High School - Nurdiana; Nurdin Noni; Sahril (International Journal of Language, Education, and Literature, 2024)
Technology-mediated language acquisition presently has several intricate issues surrounding the role of digital technologies in enhancing language learning possibilities. The present research investigated the correlation between students’ attitudes toward technology-mediated English Learning and their English achievement. The students' attitudes were assessed in terms of three components: affection, cognitive, and behavioral. Data were collected using two standards: questionnaire and document, as the students’ grade in English learning was considered their achievement. Data analysis was performed in SPSS version 26 using Pearson’s Product Moment Correlation. The results indicated no statistically significant correlation between students' attitudes towards technology-mediated English learning and their English achievement (p=.858). However, the results indicated that students generally have a positive attitude toward the use of technology in the English learning process in the classroom. The students' English Achievement was very good. Given the students' positive attitude with technology-mediated, it could use the capacities and strengths of technology-mediated to ensure the quality of English learning. Furthermore, Teachers could grant students the independence to utilize technology during their learning process or incorporate technology into the curriculum to enhance student engagement and motivation and foster an interactive classroom environment.